Prolonged administration of total glucosides of paeony improves intestinal immune imbalance and epithelial barrier damage in collagen-induced arthritis rats based on metabolomics-network pharmacology integrated analysis - Xu, Rui; Peng, Jine; Ma, Zhe; Xie, Kaili; Li, Meijing; Wang, Qi; Guo, Xiaomeng; Nan, Nan; Wang, Sihui; Li, Jing; Xu, Jingjing; Gong, Muxin (Frontiers in Pharmacology, 2023)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease characterized by synovial inflammation and joint damage with complex pathological mechanisms. In recent years, many studies have shown that the dysregulation of intestinal mucosal immunity and the damage of the epithelial barrier are closely related to the occurrence of RA. Total glucosides of paeony (TGP) have been used clinically for the treatment of RA in China for decades, while the pharmacological mechanism is still uncertain. The purpose of this study was to investigate the regulatory effect and mechanism of TGP on 2 intestinal immunity and epithelial barrier in RA model rats. The results showed that TGP alleviated immune hyperfunction by regulating the ratio of CD3 + , CD4 + and CD8 + in different lymphocyte synthesis sites of the small intestine, including Peyer's patches (PPs), intraepithelial lymphocytes (IELs), and lamina propria lymphocytes (LPLs).Specially, TGP first exhibited immunomodulatory effects on sites close to the intestinal lumen (IELs and LPLs), and then on PPs far away from the intestinal lumen as the administration time prolonged. Meanwhile, TGP restores the intestinal epithelial barrier by upregulating the ratio of villi height (V)/crypt depth (C) and expression of tight junction proteins (ZO-1, occludin). Finally, the integrated analysis of metabolomics-network pharmacology was also used to explore the possible regulation mechanism of TGP on the intestinal tract. Metabolomics analysis revealed that TGP reversed the intestinal metabolic profile disturbance in CIA rats, and identified 32 biomarkers and 163 corresponding targets; network pharmacology analysis identified 111 potential targets for TGP to treat RA. By intersecting the results of the two, three key targets such as ADA, PNP and TYR were determined. Pharmacological verification experiments showed that the levels of ADA and PNP in the small intestine of CIA rats were significantly increased, while TGP significantly decreased their ADA and PNP levels. In conclusion, purine metabolism may play an important role in the process of TGP improving RA-induced intestinal immune imbalance and impaired epithelial barrier.